PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMA MUHAMMADIYAH SURAKARTA - Aris Tri Haryanto, Farah Nuranidia, Liliek Winarni & (Transformasi, 2017)
This research aims to find out the role of principals in improving teacher’s performance at SMAMuhammadiyah Surakarta 2. The method used in this research uses qualitative descriptive.Data collection techniques in research were observation, interviews, and documentation.Researchers using theory of Mulyasa (2009) with 7 indicators. From the results of the analysis itcan be concluded that the principal already did its role properly and effectively. But there wereseveral obstacles, namely the lack of human resources in equalization perspective and lack ofoperational funds.Key words: school principal, teacher, performace